A STUDY ON THE ABILITY IN LISTENING COMPREHENSION ON DESCRIPTIVE TEXT BY THE 2nd SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP-UR - Ristanti, Septia Ristanti Septiana; Sumbayak, Desri Maria Sumbayak Maria; ', Eliwarti Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: English is the most popular and most spoken language in the world which has been used effectively in many developing countries. One of the first skills that students should be learnt in English is listening. In learning language, students use listening to began the process of learning to comprehend and produce language. The problems that usually faced by students while listening are lack of control over the speed at which speakers speak, inability to concentrate (topic, effort, technical problems), and also established learning habit in listening perfectionism.This descriptive research was conducted in order to find out the students’ ability in listening comprehension on descriptive text. The data were collected using test in the form of multiple choice. The test covered four components of listening comprehension question; finding main idea, finding detail, identifying inference, and identifying restatement.The sample of this research was the second semester students of English study program of FKIP-UR who had passed English Listening1 subject in first semester. They consisted of 3 classes: A, B, and C, and using cluster sampling technique, class B was chosen as the sample of this research. Before the data were collected, the try out was conducted in order to make sure that the test was good and valid. There were 7 rejected items and those items were revised before having been distributed to the sample. From the data analysis, it was found out that the students’ ability in listening comprehension on descriptive text was in poor level with the average score 48.33. The result of the students’ ability on listening comprehension of descriptive text was in poor level for finding main idea (44.81),identifying restatement (40.37), while finding detail was in good level (60.37), and for identifying inference was in average level (50.00).Based on the finding, it was suggested that the students need to improve their listening ability by practicing more on listening exercise and should motivate themselves to listen more listening materials. Other researchers can also focus on how to overcome the high level of difficulty of listening comprehension materials, particularly in listening to descriptive text.Key words: Ability, Listening, Comprehension, Descriptive text